A Rare Case of Congenital Simple Cystic Ranula in a Neonate - Gautam Bir Singh; Anil K. Rai; Rubeena Arora; Sunil Garg; Pooja Abbey; Shailaja Shukla (Case Reports in Otolaryngology)
Congenital ranula in a neonate is an uncommon occurrence. We present one such case of the said lesion where the clinical presentation and management were found to be interesting, hitherto unreported in the medical literature. This clinical record also reviews the scant medical literature on congenital ranula in neonates.